Use of Coffee Pulp and Minerals for Natural Soil Ameliorant - Pujiyanto Pujiyanto (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2007)
In coffee plantation, solid waste of coffee pulp is usually collected as heap nearby processing facilities for several months prior being used as compost. The practice is leading to the formation of odor and liquid which contaminate the environment. Experiments to evaluate the effect of natural soil ameliorant derived from coffee pulp and minerals were conducted at The Indonesian Coffee and Cocoa Research Institute in Jember, East Java. The experiments were intended to optimize the use of coffee pulp to support farming sustainability and minimize negative impacts of solid waste disposal originated from coffee cherry processing. Prior to applications, coffee pulp was hulled to organic paste. The paste was then mixed with 10% minerals (b/b). Composition of the minerals was 50% zeolite and 50% rock phosphate powder. The ameliorant was characterized for their physical and chemical properties. Agronomic tests were conducted on coffee and cocoa seedling. The experiments were arranged according to Randomized Completely Design with 2 factors, consisted of natural ameliorant and inorganic fertilizer respectively. Natural ameliorant derived from coffee pulp was applied at 6 levels: 0, 30, 60, 90, 120 and 150 g dry ameliorant/seedling of 3 kg soil, equivalent to 0, 1, 2, 3, 4 and 5% (b/b) of ameliorant respectively. Inorganic fertilizer was applied at 2 levels: 0 and 2 g fertilizer/application of N-P-K compound fertilizer of 15-15-15 respectively. The inorganic fertilizer was applied 4 times during nursery of coffee and cocoa. The result of the experiment indicated that coffee pulp may be used as natural soil ameliorant. Composition of ameliorant of 90% coffee pulp and 10% of minerals has good physical and chemical characteristics for soil amelioration. The composition has high water holding capacity; cations exchange capacity, organic carbon and phosphorus contents which are favorable to increase soil capacity to support plant growth. Application of ameliorant derived from coffee pulp increased significantly growth of coffee and cocoa seedling. There was positive interaction effect between the ameliorant and the fertilizers. Both the ameliorant and the fertilizers affected the seedling growth synergistically. Application of the ameliorant increased efficiency of the fertilizer. Key words: waste, coffee pulp, soil ameliorant, mineral.